Mobilization in the European public sphere: the struggle over genetically modified organisms - Tosun, Jale; Bulian, Simon (Review of policy research, 2017)
The objective of this study is to investigate the extent to which supporters and opponents at the European Union (EU) level strive to mobilize the public with regard the issue of genetically modified organisms (GMOs). To this end, it addresses two research questions: First, to which concepts do GMO opponents and supporters refer when seeking to mobilize the public? Second, do GMO opponents and supporters differ in the coherence of the concepts they use to attain public mobilization? The empirical findings show that the pro-GMO coalition is composed of biotechnology companies as well as representatives of Argentina, Canada, the United Kingdom, the United States, and the World Trade Organization. The anti-GMO coalition consists of environmental nongovernmental organizations and representatives from most of the EU member states. Altogether, the anti-GMO coalition has been more coherent in the concepts they invoke in the last few years.
Gesehen am 19.07.2017